Q-Absorbance Ratio Spectrophotometric Method for the Simultaneous Estimation of Rifampicin and Piperine in their Combined Capsule Dosage - Jenil C. Khamar, Satish A. Patel (Journal of Applied Pharmaceutical Science)
The present manuscript describe simple, sensitive, rapid, accurate, precise and economical Q-absorbance ratio method for the simultaneous determination of Rifampicin and Piperine in combined capsule dosage form. Absorbance ratio method uses the ratio of absorbances at two selected wavelengths, one which is an isoabsorptive point and other being the λ-max of one of the two components. Rifampicin and Piperine show an isoabsorptive point at 387 nm in methanol. The second wavelength used is 337 nm, which is the λ-max of Piperine in methanol. The linearity was obtained in the concentration range of 5-40 μg/ml for Rifampicin and 2-20 μg/ml for Piperine. The concentrations of the drugs were determined by using ratio of absorbances at isoabsorptive point and at the λ-max of Rifampicin. The method was successfully applied to pharmaceutical dosage form because no interference from the capsule excipients was found. The results of analysis have been validated statistically and by recovery studies.
Keywords: Rifampicin, Piperine, absorbance ratio method, isoabsorptive point, validation, simultaneous.